Elucidating the formation of Al-NBO bonds, Al-O-Al linkages and clusters in alkaline-earth aluminosilicate glasses based on molecular dynamics simulations - Ganisetti, Venkata Naga Sudheer; Gaddam, Anuraag; Kumar, Rajesh; Balaji, Sathravada; Mather, Glenn C.; Pascual, Maria J.; Fabian, Margit; Siegel, Renée; Senker, Jürgen; Kharton, Vladislav V.; Guénolé, Julien; Krishnan, N. M.Anoop; et al. (Physical Chemistry Chemical Physics, 2019)
Exploring the reasons for the initiation of Al-O-Al bond formation in alkali-earth alumino silicate glasses is a key topic in the glass-science community. Evidence for the formation of Al-O-Al and Al-NBO bonds in the glass composition 38.7CaO-9.7MgO-12.9Al2O3-38.7SiO2 (CMAS, mol%) has been provided based on Molecular Dynamics (MD) simulations. Analyses in the short-range order confirm that silicon and the majority of aluminium cations form regular tetrahedra. Well-separated homonuclear (Si-O-Si) and heteronuclear (Si-O-Al) cluster regions have been identified. In addition, a channel region (C-Region), separated from the network region, enriched with both NBO and non-framework modifier cations, has also been identified. These findings are in support of the previously proposed extended modified random network (EMRN) model for aluminosilicate glasses. A detailed analysis of the structural distributions revealed that a majority of Al, 51.6%, is found in Si-O-Al links. Although the formation of Al-O-Al and Al-NBO bonds is energetically less favourable, a significant amount of Al is found in Al-O-Al links (33.5%), violating Lowenstein's rule, and the remainder is bonded with non-bridging oxygen (NBO) in the form of Al-NBO (Al-O-(Ca, Mg)). The conditions necessary for the formation of less favourable bonds are attributed to the presence of a high amount of modifier cations in current CMAS glass and their preferable coordination.
CRIS-Team Scopus Importer:2019-11-15

The origin of deformation induced topological anisotropy in silica glass - Ganisetti, Venkata Naga Sudheer; Atila, Achraf; Guénolé, Julien; Prakash, Aruna; Horbach, Jürgen; Wondraczek, Lothar; Bitzek, Erik (Acta Materialia, 2023)
Oxide glasses with a network structure are omnipresent in daily life. Often, they are regarded as isotropic materials; however, structural anisotropy can be induced through processing in mechanical fields and leads to unique materials properties. Unfortunately, due to the lack of local, atomic-scale analysis methods, the microscopic mechanisms leading to anisotropy remained elusive. Using novel analysis methods on glasses generated by molecular dynamics simulations, this paper provides a microscopic understanding of topological anisotropy in silica (SiO2) glass under mechanical loads. The anisotropy observed in silica glass originates from a preferred orientation of SiO4 tetrahedra at both short- and medium-range levels that can be controlled via the mode of mechanical loading. The findings elucidate the relation between the deformation protocol and the resulting anisotropic structure of the silica network (involving both persistent and transient effects), and thus provide important insight for the design of oxide glasses with tailored materials properties.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Molecular dynamics; Plasticity; Silica glass; Stereographic projection